A case study of ISO TS16949 implementation and its results - Miguel, Paulo Augusto Cauchick; Leal, Andréa Fort; Silva, Íris Bento da (Revista Gestão da Produção Operações e Sistemas, 2008)
This research presents a case study on the implementation of ISO TS 16949 and its results in autoparts company. The aim is to investigate how were the results of this implementation and how was the strategy used by the company to obtain the certification. To achieve this aim, a case study was used as a research strategy, taking data from interviews, observation in the work environment and documentation analysis. After the presentation of the theory, the results from case study are presented. Analysing theses results, it is possible to conclude that the company organization during the preparation for certification, provided the ISO TS 16949 certification, because the strategy adopted was able to identify all the necessary work, the allocate resources to execute this work and to plan auditing to achieve its objectives. Key-words: quality system, quality management, ISO TS 16949, case study.